Prevalence of tuberculosis in bovines in Pakistan during 2000–2024: a systematic review and meta-analysis - Sehrish, Siddique; Liu, Xue-Tong; Lou, Wen-Bo; Zhang, Shu-Ying; Ata, Emad Beshir; Yang, Ge-Gui; Wang, Qi; Zeng, Fan-Li; Leng, Xue; Shi, Kun; Azeem, Riaz-Muhammad; Gong, Qing-Long; et al. (Frontiers in Veterinary Science, 2025)
BackgroundBovine tuberculosis (bTB) primarily caused by Mycobacterium bovis (M. bovis), is a globally prevalent zoonotic infectious disease of cattle and other livestock and wildlife species. Pakistan is the fourth-largest milk-producing country in the world, with approximately 212 million animals. Livestock farming provides a livelihood for almost 8 million families. Moreover, there is currently no effective control program and national data in place. Therefore, we constructed a first meta-analysis on the prevalence of bovine tuberculosis in Pakistan. This study aimed to provide an overview of bovine tuberculosis in this country and identify the risk factors associated with its prevalence.MethodsWe searched Science Direct, Pubmed, Base, Green File-Poly U Library, Google Scholar, and additional articles were also identified manually from reference lists of articles generated in database search, systemically for papers that presented bTB prevalence data, published in English language between January 1, 2000, and April 30 2024. A total of 35 published articles were selected for inclusion in the meta-analysis.ResultsThe estimated overall prevalence of bTB was found to be 6.06% [95% CI: 4.67–7.87]. Cattle were more susceptible to infection, with a higher prevalence (6.44% [95% CI: 4.04–10.26]) compared to buffalo (5.54% [95% CI: 3.13–9.81]). The prevalence determined by PCR (5.65% [95% CI: 3.33–5.98]) was much similar to that of TST (5.61% [95% CI: 4.20–7.50]) with no significant difference. Milk samples showed the highest prevalence (14.66% [95% CI: 7.38–29.11]), particularly due to the consumption of unpasteurized milk, improper handling of dairy products and suckling by calves from the infected cows. Furthermore, the analysis considered effect of various potential risk factors (age, weight, breed, body condition score, herd size, animal status) along with different geographical factors (longitude, latitude, altitude, humidity, rainfall, temperature, climate) associated with bTB prevalence, which should be considered when developing future disease surveillance and control programs.ConclusionIn Pakistan bTB was widely distributed throughout the country, as a neglected zoonotic disease. Long-term disease prevalence monitoring should be recommended along with the need to improve diagnostic techniques, enhance farm management practices, and implement targeted surveillance to protect both animal and public health.